2009
DOI: 10.1007/s11239-009-0319-1
|View full text |Cite
|
Sign up to set email alerts
|

The actuarial survival analysis of the surgical and non-surgical therapy regimen for chronic thromboembolic pulmonary hypertension

Abstract: The PTE procedure has statistically superiority over thrombolytic therapy for the proximal type of CTEPH in terms of actuarial survival; however, for the distal type of CTEPH, the PTE procedure provides no benefits with regard to actuarial survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…Only the most recent publications with the most complete data set from each institute were retained. As a result, 19 studies 6,15,21,22,25,26,29,30,33,35,36,38,40,[42][43][44][46][47][48] with a total number of 2729 patients were included for appraisal and data extraction ( Table 2).…”
Section: Quantity Of Evidencementioning
confidence: 99%
See 3 more Smart Citations
“…Only the most recent publications with the most complete data set from each institute were retained. As a result, 19 studies 6,15,21,22,25,26,29,30,33,35,36,38,40,[42][43][44][46][47][48] with a total number of 2729 patients were included for appraisal and data extraction ( Table 2).…”
Section: Quantity Of Evidencementioning
confidence: 99%
“…Four prospective studies were identified, 30,38,40,46) ; other studies were either clearly retrospective 6,15,22,25,29,35,42,44,47,48) or not specified. 21,26,33,43) Two studies presented results in a series of CTEPH patients treated surgically and medically 40,47) ; others included only series of surgically treated patients. There was one retrospective study from Austria that compared hemodynamic indices between PTE and non-PTE patients with a 1-year follow-up, but could not be included in the current review due to insufficient data to meet the inclusion criteria.…”
Section: Quality Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Other parts of the world, including India [13], China [14,15], and Russia [16], have reported improved outcomes after pulmonary endarterectomy, and surgical techniques and expertise are improving. On the other hand, in Japan for example, balloon pulmonary angioplasty (BPA) as a treatment for CTEPH is emerging [17] at least in part due to lack of surgical expertise in and/or availability of pulmonary endarterectomy, cultural reasons, and the available expertise in percutaneous interventional therapies.…”
mentioning
confidence: 99%